2019
DOI: 10.3390/medicina55100702
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis and Lung Transplantation: When it is Feasible

Abstract: Despite the availability of antifibrotic therapies, many patients with idiopathic pulmonary fibrosis (IPF) will progress to advanced disease and require lung transplantation. International guidelines for transplant referral and listing of patients with interstitial lung disease are not specific to those with IPF and were published before the widespread use of antifibrotic therapy. In this review, we discussed difficulties in decision-making when dealing with patients with IPF due to the wide variability in cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…[82][83][84] Generally accepted benchmarks for lung transplant referral as well as contraindications to the procedure are based on guidelines proposed by the International Society of Heart and Lung Transplantation (ISHLT). 77,85 Among the key criteria for placement on the transplant list are rapid decline in FVC or DL CO , oxygen desaturation, or decrease in distance covered during 6-min walk test, pulmonary hypertension, or hospitalization due to respiratory decline, pneumothorax, or acute exacerbation. Importantly, telomere shortening and mutations in genes that control telomere function such as Telomerase Reverse Transcriptase (TERT) and Telomerase RNA Component (TERC) are associated with familial and sporadic cases of IPF and this may be considered in transplant decision-making.…”
Section: Nonpharmacologic Therapy: Lung Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…[82][83][84] Generally accepted benchmarks for lung transplant referral as well as contraindications to the procedure are based on guidelines proposed by the International Society of Heart and Lung Transplantation (ISHLT). 77,85 Among the key criteria for placement on the transplant list are rapid decline in FVC or DL CO , oxygen desaturation, or decrease in distance covered during 6-min walk test, pulmonary hypertension, or hospitalization due to respiratory decline, pneumothorax, or acute exacerbation. Importantly, telomere shortening and mutations in genes that control telomere function such as Telomerase Reverse Transcriptase (TERT) and Telomerase RNA Component (TERC) are associated with familial and sporadic cases of IPF and this may be considered in transplant decision-making.…”
Section: Nonpharmacologic Therapy: Lung Transplantationmentioning
confidence: 99%
“… 82 , 83 , 84 Generally accepted benchmarks for lung transplant referral as well as contraindications to the procedure are based on guidelines proposed by the International Society of Heart and Lung Transplantation (ISHLT). 77 , 85 Among the key criteria for placement on the transplant list are rapid decline in FVC or DL CO , oxygen desaturation, or decrease in distance covered during 6‐min walk test, pulmonary hypertension, or hospitalization due to respiratory decline, pneumothorax, or acute exacerbation.…”
Section: Nonpharmacologic Therapy: Lung Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“… 91 Because the observational IPF Prospective Outcomes (IPF-PRO) Registry found that mortality was independently associated with patient-reported increasing symptom burden and reduced tolerance of physical activity, these manifestations should prompt early referral for lung transplant evaluation. 92 , 93 Although they are beyond the scope of this review, the International Society for Heart and Lung Transplantation has published guidelines for timing lung transplantation in IPF patients based upon various prognostic indicators. 91 …”
Section: Treatment Guidelines: Lung Transplantationmentioning
confidence: 99%
“…While two anti-fibrotics have been clinically approved, they only slow the progression of the disease. The definitive treatment for end-stage lung fibrosis remains lung transplant, which has a median survival as low as 50% at five years post-operation (6). Given the poor prognosis, it is imperative to prevent the development of lung fibrosis before it can progress to end stage disease.…”
Section: Introductionmentioning
confidence: 99%